The Comparison of Contact with Inmates, Risk Perception, and Mental Health of Officers in a Correctional Institution with Different Levels of Security - Imaduddin Hamzah; Umar Anwar; Vivi Sylviani Biafri; Qisthina Aulia (HM Publisher, 2022)
Introduction: Correctional institutions (LP) have various levels of security that are adjusted to the characteristics of the inmates accommodated in it. This level of security includes minimum, medium, and maximum prisons and often includes special prisons for prisoners with special needs or high danger. Differences in security levels present unique dynamics and challenges in contact between officers and inmates, perceptions of risk, and their impact on officers' mental health. Methods: This study is an analytic observational study with a cross-sectional approach. A total of 116 research subjects participated in this study. This study observes contact between officers and inmates using the contact with inmate scale. Perception of risk is measured by a scale compiled by Ferdik. The mental health assessment of correctional worker participants used the mental health inventory (MHI-38) made by Veit and Ware. Results: Officers in medium-security level penitentiaries have more positive contact with inmates than in maximum and super-maximum security level penitentiaries. Likewise, the aspect of officer risk perception in medium-security level penitentiaries shows a lower score than in maximum and super-maximum security level penitentiaries. However, super-maximum security level penitentiary officers show a lower level of mental health than medium security level penitentiaries. Conclusion: There are differences in correctional officers' contact with inmates, risk perception, and mental health of correctional officers in prisons with different levels of security.